Finland : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2005)
This Report on the Observance of Standards and Codes data module provides an assessment of Finland's macroeconomic statistics against the Special Data Dissemination Standard complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework, July 2003. The report reveals that Finland's macroeconomic statistics are of generally high quality. They are adequate to conduct effective surveillance. Finland's statistical managers are highly aware of all dimensions of quality. However, some shortcomings may detract from the accurate and timely analysis of economic and financial developments and the formulation of appropriate policy.